HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN PERILAKU AGRESIF REMAJA - Reshalia, Reshalia; Zulfitri, Reni; Bayhakki, Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adolescence is a very critical period in human development stage. Adolescent will find more problems, one of the prombem is psychosocial problem, that is aggressive behavior. The purpose of this research is to know the correlation between family social support and aggressive behavior in adolescent. The design of this research was descriptive correlation using cross sectional approach. The sample of this research were 135 students of Tri Bhakti Junior High School Pekanbaru using stratified random sampling technique. The data were collected by using familys social support questionnaire and aggression questionnaire, questionnaire has been tested its validity and reliability. The univariate analysis was used to know the frequency of distribution and bivariate analysis was used chi-square test. The result from 82 respondents with positive family social support showed, 24 respondents (29,3%) had high aggressive behavior and 58 respondents (70,7%) had low aggressive behavior. Then, from 53 respondents with negative family social support, 30 respondents (56,6%) had high aggressive behavior and 23 respondents (43,4%) had low aggressive behavior. The result of chi-square test showed that p value = 0,003 <Î± = (0,05). It can be conclude that there was significant correlation between family social support and aggressive behavior in adolescent. Family have to increase the quality of social support to adolescent, so it will decrease the risk of aggressive behaviour in adolescent. Â Keywords: Adolescent, aggressive behaviour, family social support